TWO-SIDED DILEMMA OF INDONESIAN COMMUNITY'S PERSONAL INFORMATION USE IN THE DIGITAL ERA - Bob Indiarto Agus Susatyo; Udi Rusadi (International Journal of Social Science, 2024)
This research is based on the thoughts of Oscar H. Gandy, (2014) regarding The Political Economy of Personal Information which has implications for the phenomena currently occurring in Indonesia. The researcher intends to describe what the political and economic dilemmas of managing personal information problems are like, the extent of the problem of awareness of the value of personal information and future challenges in Indonesian society. The approach used is digital communication and political economy. Meanwhile, the method chosen is a qualitative method of literature study. Data sources use secondary data from literature in the form of books, journals or scientific research, documents and various related news articles. The result of this research is the political-economic dilemma of managing personal information problems using the analogy of two sides of a knife. On the one hand, the positive impact of managing personal information well and according to regulations can provide opportunities to open new businesses with data as a valuable commodity. On the other hand, the negative impact of the digital capitalism business model regarding personal data and information makes society an object that will be filled with various forms of communication programs with the aim of creating a consumer culture. Then, in looking at the main weakness in the development of this personal information problem, it is that people still have low awareness of the importance and value of the information they have